A Review of Female Data from TAVR Trials - Parry, Nicola (MD Conference Express, 2014)
This article discusses female data from trials of patients undergoing transcatheter aortic valve replacement (TAVR). Specific trials include the ADVANCE and WIN TAVI registries, as well as the CoreValve and PARTNER trials.